Unmet health needs of elderly: a community based cross-sectional study in rural areas of Kancheepuram District, Tamil Nadu - Kalusivalingam, N.; Bobhate, Prateek; Kalaivani, A.; Karnaboopathy, R. (International Journal Of Community Medicine And Public Health, 2020)
Background: The proportion of elderly population is on the increasing trend in India. Morbidity was found higher among the elderly population. About 10% increased risk of mortality was found among elderly people with unmet needs. The objective of the study was to assess the morbidity pattern and unmet health needs among elderly population in rural areas of Kancheepuram district, Tamil Nadu. Methods: This community based cross-sectional study was conducted for a period of 18 months in four selected villages in Kancheepuram district, Tamil Nadu, among 390 participants. EASY care standard (2010) questionnaire was used for assessment of health care needs. Frequency distribution of study variables and association using chi-square test were done using SPSS software version 23. Results: Out of 390 study participants, 51% were females. The most common morbidity was arthritis (40.5%), followed by diabetes and difficulty in hearing (29.5% each). Psycho-social issues such as loneliness (36.7%), little interest in doing things (30.8%), feeling hopelessness (30%) were noted among the study participants. The highest unmet health need was 11.8% for difficulty in hearing. The unmet health needs were associated with older age, widowhood, lower educational status, inability to work, low socio-economic status, absence of individual income, and absence of care taker of the study participants. Conclusions: The health needs of elderly are multi-faceted viz., medical, psycho-social, financial, etc. Since, family characteristics play a major role in meeting the health needs of elderly population, community-oriented services mainly involving family members will help for addressing the unmet needs of the elderly.